Optimizing Vocational Civic Education For The Development Of Student Character - Yudha Pradana; Dadang Sundawa (Al-Makki Publisher, 2023)
In terms of being students, civic education is very closely related to the development of the character of citizens. In this case, vocational civics can also be developed and given to vocational higher education students. This research aims to find out about civics learning in vocational universities and the character development of students through vocational civics learning. The method carried out is research and development with the ADDIE model. The results showed that learning was carried out contextually and cooperatively with a project-based learning approach supported by 21st century skills. Learning develops citizen competencies in the form of knowledge, disposition, and skills. The character of students is developed in the forms of critical thinking, creativity, discipline, appreciation of work, and curiosity. In addition, with the vocational education approach, the aspects developed in vocational civics are communication skills, critical and creative thinking, information literacy, digital literacy, inquiry skills, interpersonal skills, multicultural literacy, problem solving, and technology skills. Meanwhile, support in the form of 21st century skills is shown through communication, collaboration, creativity, and critical thinking.